The Analysis of Circumstantial Adjuncts in Jakarta Post Headlines News - Ratna Sari Dewi (English Teaching and Linguistics Journal (ETLiJ), 2021)
The purpose of this research is to describe the types of adjuncts and the dominant types of circumstantial adjunct that found in Jakarta Post headlines News  because it expresses the meaning through sentences. This qualitative descriptive research used library research and documentation method. The data in Jakarta Post headline news dated 5th January 2021 from the two articles entitled “Israel is the fastest in the Covid-19 vaccination program, PM Netanyahu estimates the country is pandemic free in February “ and “Japan’s indigenious people, the Ainu, were the earliest settlers of Hokkaido, Japan’s Northern island be the sources of data. There are 202 circumstantial adjuncts found in these headline news. Then, the data selected based on the topic discussion by identifying and making a list from those sentences in the headlines news. After that, data were analyzed by using Halliday’s theory and then classified these adjuncts and calculated the percentage of the adjunct’s occurrences. Through this study, it was discovered that there were eight circumstantial  types of adjuncts used in this headlines news such as location, extent, role, manner, accompaniment, cause, matter and angle but there is no circumstantial adjuncts of contingency in these articles. Besides, it was also found that location adjunct became the most dominant adjuncts with the percentage 42.57 %.